The use of kenaf fibre as an alternative laminated composite for production of prosthetic leg socket - Md Tahir, Paridah; Ibrahim, Rahinah; Che Me, Rosalam (2014)
The present invention provides a laminated composite material for prosthetic application, the laminated composite material includes: a) at least two layers of woven kenaf fibres laminated in sandwiched, alternating interlace with Nylon Stockinette layers; and b) at least one layer of Polivynil Alcohol (PVA) laminated at outer surfaces of lamination structure; wherein mechanical and physical properties of the laminated composites differ in terms of the arrangement and number of layers of material used in the lamination structure.